Voice over IPv6 architectures for next generation VoIP networks - Minoli, Daniel, 1952- (Burlington, MA : Newnes, 2006)
IPv6 (Internet Protocol version 6) is the future of Internet telephony. And this book is your guide to that future. IPv6 is the replacement for the currently used IPv4 (Internet Protocol version 4). IPv6 will offer increased IP addresses (full 128-bit addresses, compared to the 32-bit addresses of IPv4), enhanced security, and greater robustness. It will also be fully backwards compatible with existing IPv4 systems. These capabilities will finally make Internet telephony a viable competitor to conventional switched telephone networks. In this book, Dan Minoli clearly explains IPv6 and how telephone networks can be built on its foundations. This is not just another IPv6 book; instead, it focuses on those aspects of IPv6 relevant to Internet telephony systems and voice networks. Minoli uses a compare/contrast approach, exploring where IPv6 is similar to IPv4 and where it differs, to let you quickly grasp the essence of IPv6 and the similarities (and differences) between current IPv4-based systems and IPv6-based systems. If you will be designing, implementing, or maintaining the next generation of Internet telephony systems, then you need the information in this book! *Explains the essential concepts of IPv6 and how they relate to Internet telephony *Describes how Internet telephony systems using IPv6 are different from, and better than, Internet telephony systems based on the older IPv4 standard *Discusses how to transition existing IPv4 Internet telephony systems and conventional switched systems to IPv6-based systems *Extensive treatment of security issues, including IP layer encryption and authentication methods *Explains connection techniques, including plug and play approaches, for equipment used in IPv6 systems * The first title describing how the next generation Internet protocolIPv6can be used for Internet telephony * Explains IPv6 as it applies to Internet telephony (VoIP) * Shows how IPv6 gives better security, QoS, and signal integrity in Internet telephony.
Basic VoP/VoIP concepts -- Basic VoIP signaling and SIP concepts -- Basic "presence" concepts -- Issues with current VoIP technologies -- Basic IPv6 concepts -- Using IPv6 to support 3G VoIP -- Issues related to transitioning to IPv6.
Includes bibliographical references (p. 343-347) and index.
Keywords: Internet telephony; Electronic books